Protection Against Acute, Ascending Pyelonephritis Caused by Escherichia coli in Rats, Using Isolated Capsular Antigen Conjugated to Bovine Serum Albumin - Kaijser, B. (1983)
We found that isolated Escherichia coli K13 antigen conjugated to bovine serum albumin, in contrast to isolated, non-conjugated K13, was highly immunogenic and induced protection against acute pyelonephritis caused by E. coli O6K13H1 in rats.